ANNOTATED BIBLIOGRAPHY OF THE RUSSIAN LANGUAGES LITERATURE ON GLACIOLOGY FOR 2016 - V. M. Kotlyakov; L. P. Chernova (Лëд и снег, 2018)
The proposed annual bibliography continues annotated lists of the Russian‑language literature on glaciology that were regularly published in the past. It includes 345 references grouped into the following ten sections: 1)  general issues of glaciology; 2)  physics and chemistry of ice; 3)  atmospheric ice; 4)  snow cover; 5)  avalanches and glacial mudflows; 6) sea ice; 7) river and lake ice; 8) icings and ground ice; 9) the glaciers and ice caps; 10) palaeoglaciology. In addition to the works of the current year, some works of earlier years are added, that, for various reasons, were not included in previous bibliographies.